KLASIFIKASI ILMU PENGETAHUAN MENURUT IMĀM Al-GHAZĀLĪ - Indra Ari Fajari (IAIN Tulungagung, 2016)
Al-Ghazali categorizes science into two categories; namely fardu ‘ain andfardu kifayah. According to al-Attas, al-Ghazali has prioritized the contentof knowledge rather than method. However, this does not mean that al-Ghazali ignores method. al-Ghazali believes that the glory of science depends on the result and the authenticity of its principles or watha>qat al-dalil wa qawwatihi, and the firts is more essential than the second. For instance, though medical science is not as precise as mathematics, the prior is more essential for an individual than the later. Likewise, religious science is more noble than medical science. So, if the curriculum of islamic education refers to Ghazali’s classification of science, the prioritized learning isin terms of content that is the dignity of science itself. Therefore, the content of islamic education curriculum shoud be started from fardu ‘ain to fardu kifayahKeywords: classification, fardu ‘ain, fardu kifayah, knowledge, al-Ghazali